2011
DOI: 10.1099/mic.0.048215-0
|View full text |Cite
|
Sign up to set email alerts
|

Gentisate and 3-oxoadipate pathways in the yeast Candida parapsilosis: identification and functional analysis of the genes coding for 3-hydroxybenzoate 6-hydroxylase and 4-hydroxybenzoate 1-hydroxylase

Abstract: The pathogenic yeast Candida parapsilosis degrades various hydroxy derivatives of benzenes and benzoates by the gentisate and 3-oxoadipate pathways. We identified the genes MNX1, MNX2, MNX3, GDX1, HDX1 and FPH1 that code for enzymes involved in these pathways in the complete genome sequence of C. parapsilosis. Next, we demonstrated that MNX1, MNX2, MNX3 and GDX1 are inducible and transcriptionally controlled by hydroxyaromatic substrates present in cultivation media. Our results indicate that MNX1 and MNX2 cod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
64
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(70 citation statements)
references
References 30 publications
(46 reference statements)
5
64
0
Order By: Relevance
“…Homologous genes are enclosed in a genomic insert of five highly conserved genes (Maguire et al, 2013) (Supplemental Table S4 and Fig. S5) that is highly correlated to phenol and catechol degradation capacity in Ascomycota yeasts (Holesova et al, 2011;Middelhoven, 1993;Tsai and Li, 2007). One of the insert genes is homologous to AN4061 that in salicylate medium was up-regulated and its encoded protein also increased (Table 2).…”
Section: The Catechol Branch Of the 3-oxoadipate Pathwaymentioning
confidence: 96%
See 1 more Smart Citation
“…Homologous genes are enclosed in a genomic insert of five highly conserved genes (Maguire et al, 2013) (Supplemental Table S4 and Fig. S5) that is highly correlated to phenol and catechol degradation capacity in Ascomycota yeasts (Holesova et al, 2011;Middelhoven, 1993;Tsai and Li, 2007). One of the insert genes is homologous to AN4061 that in salicylate medium was up-regulated and its encoded protein also increased (Table 2).…”
Section: The Catechol Branch Of the 3-oxoadipate Pathwaymentioning
confidence: 96%
“…A member of the first sub-group, previously characterised and identified in Candida albicans (Tsai and Li, 2007), is orthologous to AN4532 and AN8998 (paralogous genes). Candida parapsilosis utilises benzoate (and derivatives) through a hydroxyquinol variant of the 3-oxoadipate pathway, hence its single catechol dioxygenase-like gene belongs to the second sub-group (Holesova et al, 2011), which is orthologous to AN0764 and AN9363. These findings support AN8566 as the protocatechuate 3,4-dioxygenase gene (Table 2 and Fig.…”
Section: The Protocatechuate Branch Of the 3-oxoadipate Pathwaymentioning
confidence: 99%
“…It is most likely that SA is converted directly to catechol by oxidative decarboxylation, because a simple decarboxylation will produce phenol first, and phenol does not appear to be a precursor for veratrole (Supplemental Table S1). While the enzymatic conversion of SA to catechol has not yet been documented in plants, it has been reported that yeast and microbes oxidatively decarboxylate SA to catechol as part of the modified 3-oxoadipate and meta-cleavage pathways (You et al, 1990;Eppink et al, 1997;Bosch et al, 1999;Holesova et al, 2011).…”
Section: Veratrole Emission During the Day/night Cyclementioning
confidence: 99%
“…In the pathogenic yeast Candida parapsilosis , these compounds are metabolized via the hydroxyhydroquinone (HHQ) variant of the 3-oxoadipate pathway (3-OAP) and the glutathione-dependent variant of the gentisate pathway (GP) (Middelhoven et al 1992; Middelhoven 1993). Previously, we have identified C. parapsilosis genes MNX1 , MNX2 , MNX3 , GDX1 , HDX1 , and FPH1 coding for components of both pathways (Holesova et al 2011). We have found that the genes coding for key enzymes of the GP and 3-OAP are organized in two metabolic clusters (Holesova et al 2011; Gerecova et al 2015).…”
mentioning
confidence: 99%